High risk and early onset of cancer in Chinese patients with Peutz-Jeghers syndrome - Wang, Zhiqing; Wang, Zhi; Wang, Ying; Wu, Jianhua; Yu, Zonglin; Chen, Chudi; Chen, Junsheng; Wu, Baoping; Chen, Ye (Frontiers in Oncology, 2022)
Peutz-Jeghers syndrome (PJS) is an autosomal dominant inherited disorder associated with a predisposition to a variety of cancers. Previous studies that have evaluated the cancer spectrum and risk of this rare disease have primarily been based on small data sets or heterogeneous cohorts from different countries. Here, we report the results of a large homogeneous cohort of Chinese PJS patients who were followed prospectively from 2006 to July 2021, and clinical data before 2006 were retrospectively collected. A total of 412 PJS patients (56.55% males) from 208 families were enrolled, contributing 12,798 person-years of follow-up. A total of 113 cancers were diagnosed in 109 patients (26.46%). The median age at the first cancer diagnosis was 40 years. In particular, patients born after the 1980s were diagnosed with cancer at an earlier median age of 30.5 years. The cumulative cancer risk was sharply increased to 30.9% at age 40 years; this high cancer risk age was 10 years earlier than that reported in previous Western studies, and increased to 76.2% at an age of 60 years. The most common cancer was gastrointestinal (GI) cancer (64.6%), in which colorectal cancer constituted a significantly larger proportional distribution (32.74%), when compared with previous investigations (11.1%−20.83%). There was some evidence that overrepresentation point variants in domain XI of STK11 may be associated with GI cancers. Furthermore, the incidences of gynecological and lung cancers were second only to that of GI cancer in this cohort. These results may provide novel insight for justifying surveillance to detect cancers at an earlier phase to improve clinical outcomes. Furthermore, the potential STK11 genotype-phenotype association could be the basis for future genetic counseling.